Gestão da informação na Pró-Reitoria de Graduação da UFRN: contributo para promoção de uma cultura informacional voltada à transparência ativa - Nunes, Camila Câmara Santiago (2019)
The publication of the Access to Information Law (LAI), in the year of 2011, meant the establishment of the right to access public information in Brazil, already guaranteed by the Brazilian Constitution of 1988. The aforementioned rule presents as basic principle the active transparency which is configured by spontaneous disclosure of information by the Public Administration. In many institutions the expansion of this practice is already noted; on the other hand, institutions need to understand that a proper information management is not accomplished only by using modern information systems; also, change information culture of organizations is fundamental, aiming a full adaptation to a new scenario. Thus, this work approach themes related to organizational culture, information culture and behavior, and also its contributions, along with information management, to develop an information culture in the process to meet the demands of access to information that naturalizes the active transparency at the Pro-rectory of Graduation (PROGRAD) of the Federal University of Rio Grande do Norte (UFRN). Therefore, this research presents as general objective to analyze if exists an information culture established in the process to meet the demands of access to information received by PROGRAD that contributes to a naturalization of the active transparency practice. In order to achieve the general objective, the following specific objectives are proposed: a) To describe the information flow of the process of meeting the demands of access to information; b) To categorize information with greater demand of access and establish categories of information that encourage the practice of active transparency, according with LAI; c) To verify the presence of indicators of an information culture in the process of meeting the demands of access to information; and d) To suggest tools/instruments that promote active transparency as well as contribute to develop an information culture. The research presents a qualitative approach, applied and descriptive, also configured as a case study. Regarding the data gathering, a document analysis and semistructured interviews were performed. For data analysis, the Bardin`s (2011) method of content analysis was used. The results generated the perception that PROGRAD practices the active transparency in an incipient form; just as exists an embrionary information culture in the process to meet the demands of access to information. Furthermore, an intervention proposal was elaborated, in which was suggested to develop a common questions section in the website of PROGRAD so that can stimulate the active transparency and greater access to information by the public of the agency. Also, an action set that could develop the information culture was proposed in the aforementioned process of meeting the demands.